ANALYSIS OF PROCESSING FEASIBILITY CERTIFICATE STANDARDS AND THE IMPLEMENTATION OF GOOD MANUFACTURING PRACTICES (GMP) AND SANITATION STANDARD OPERATING PROCEDURES (SSOP) IN QINA MILKFOOD SMES IN SEMARANG, CENTRAL JAVA - Ningsih, Trisna; Panjaitan, Pola Sabar Tomohon; Soeharso, Agusta Putri Balqis Linda; Al Ghifari, Abidzar (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
The Processing Feasibility Certificate (SKP) standard plays a crucial role in ensuring a production system that is safe, hygienic, and of high quality, particularly in small-scale fish processing enterprises. UMKM Bandeng Qina in Semarang, is one such business unit that has implemented the SKP system by adopting the principles of Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP). The analysis was conducted on all processing feasibility components, with emphasis on key aspects including building conditions, sanitation facilities, personal hygiene, documentation, and quality control systems. The results indicate that most GMP and SSOP aspects have been properly implemented, enabling UMKM Bandeng Qina to be deemed eligible to conduct bandeng presto production activities and to obtain an SKP rating of B (Good). Out of the 17 assessed clauses, 7 were identified as non-conformities, consisting of 4 minor, 2 major, and 1 serious finding. Therefore, corrective actions are required in several areas, including facility structure, equipment arrangement and maintenance, wastewater treatment systems, product-contact tools and utensils, employee facilities, and worker hygiene and health practices. The implementation of SKP has demonstrated a positive impact on improving product quality, food safety, and consumer confidence in processed milkfish products. Continued supervision and strengthening of the quality management system are necessary to ensure that processing feasibility standards are consistently maintained.